Endoscopic ultrasound‐guided tissue acquisition allows a reliable proliferation assessment of small (≤20 mm) pancreatic neuroendocrine tumors - Yoshihide Nanno; Hirochika Toyama; Kazuyuki Nagai; Dongha Lee; Yuichiro Uchida; Jun Ishida; Takeshi Takahara; Ippei Matsumoto; Etsuro Hatano; Takumi Fukumoto (Annals of Gastroenterological Surgery)
Abstract Aim Evidence regarding the reliability of endoscopic ultrasound‐guided tissue acquisition (EUS‐TA) for assessing histological proliferation and WHO grading of small (≤20 mm) pancreatic neuroendocrine tumors (PanNETs) is limited. Methods In this multicenter retrospective study, we analyzed data from 122 patients with small PanNETs who underwent EUS‐TA followed by surgical resection between 2006 and 2022. We compared the histopathological proliferation assessment and WHO grading between preoperative EUS‐TA and surgical definitive specimens. Results Among the 122 patients with small PanNETs (80% with surgical definitive WHO grade G1 and 20% with G2), EUS‐TA histology identified neuroendocrine tumors in 101 (83%) patients and provided WHO grading in 85 (70%) patients. Histopathological WHO grading for EUS‐TA was concordant with surgical definitive grading in 86% (73/85) of cases, overstaged in 4% (3/85), and understaged in 11% (9/85). Moderate, severe, and fatal adverse events associated with EUS‐TA, as classified by the lexicon, were not reported in this cohort. Conclusion EUS‐TA is a reliable method for assessing histopathological proliferation and WHO grading of small PanNETs. However, grading discordance may occur, and a risk–benefit evaluation on a per‐patient basis is recommended.